Hyperprolactinemia in antipsychotic-naive patients with first-episode psychosis - Riecher-Rössler, A.; Rybakowski, J. K.; Pflueger, M. O.; Beyrau, R.; Kahn, R. S.; Malik, P.; Fleischhacker, W. W. (Psychological medicine, 2013)
Hyperprolactinemia is frequent in patients with schizophrenic psychoses. It is usually regarded as an adverse effect of antipsychotics but has recently also been shown in patients without antipsychotic medication. Our objective was to test whether hyperprolactinemia occurs in antipsychotic-naive first-episode patients (FEPs). In the framework of the European First Episode Schizophrenia Trial (EUFEST), 249 out of 498 FEPs were eligible for this study, of whom 74 were antipsychotic naive. All patients were investigated regarding their serum prolactin levels with immunoassays standardized against the 3rd International Reference Standard 84/500. Twenty-nine (39%) of the 74 antipsychotic-naive patients showed hyperprolactinemia not explained by any other reason, 11 (50%) of 22 women and 18 (35%) of 52 men. Hyperprolactinemia may be present in patients with schizophrenic psychoses independent of antipsychotic medication. It might be stress induced. As enhanced prolactin can increase dopamine release through a feedback mechanism, this could contribute to explaining how stress can trigger the outbreak of psychosis.